2013
DOI: 10.1111/cas.12216
|View full text |Cite
|
Sign up to set email alerts
|

Sustained upregulation of effector natural killer cells in chronic myeloid leukemia after discontinuation of imatinib

Abstract: A number of CML patients who achieve a sustained complete molecular response (CMR) for at least 2 years during imatinib (IM) therapy can discontinue IM without relapse. With the longterm goal of developing immunological criteria for managing IM therapy in CML patients, we compared the immunophenotypic profiles of three groups of CML patients: those who received IM and had a CMR for more than two consecutive years (CMR group); patients who received IM and did not have a sustained CMR but maintained a major mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 43 publications
(110 reference statements)
1
36
0
1
Order By: Relevance
“…A substantial proportion of such patients maintains the response for more than 12 months after discontinuation of imatinib 39 or dasatinib. 40 Notably, increases in NK cells 40,41 but not T cells 40 In conclusion, this study using PCA suggests that the distinctive NK cell subset, that is, CMV-associated adaptive NK cells, is responsible for the dasatinibinduced NK cell expansion, which likely occurs through subclinical CMV reactivation.…”
Section: Discussionmentioning
confidence: 73%
“…A substantial proportion of such patients maintains the response for more than 12 months after discontinuation of imatinib 39 or dasatinib. 40 Notably, increases in NK cells 40,41 but not T cells 40 In conclusion, this study using PCA suggests that the distinctive NK cell subset, that is, CMV-associated adaptive NK cells, is responsible for the dasatinibinduced NK cell expansion, which likely occurs through subclinical CMV reactivation.…”
Section: Discussionmentioning
confidence: 73%
“…Briefly, we observed that ESR and CRP were increased in some patients with IMWS (data not shown) but CPK were not noted in association with the musculoskeletal symptoms. The importance of immunologic status for successful TFR is illustrated by the beneficial effect of natural killer (NK) cell activity 17,18 and interferon treatment on a higher TFR rate, 4,7 indicating that the re-activation of autologous immunity may contribute to the elimination of MRD after IM discontinuation via the emergence of NK cells or cytotoxic T lymphocytes (CTLs) against CML-associated antigens. [19][20][21] Although we analyzed the frequency and function of NK cells after IM discontinuation in some patients, no significant association was found.…”
mentioning
confidence: 99%
“…Despite the well-known antitumor effect of the innate immune system, few data exist on the role of natural killer (NK) cells and their killer-cell immunoglobulin-like receptors (KIRs) in CML [6][7][8]. According to some recent reports, early disease relapse after TKI discontinuation was associated with both low numbers and impaired function of NK cells [9][10][11]. NK cells can express both inhibitory and activating KIR receptors, which recognize four exclusive epitopes carried by human leukocyte antigen (HLA)-A, -B, and -C class I molecules expressed on target cells: C1, C2, Bw4, and A3/A11 [12].…”
mentioning
confidence: 99%